(untitled) (Research, Society and Development, 2021)
This work had as objective to proceed sensorial analyses, microbiological physical-chemistries and, of comparative form, the honeys, collected for the producers and researcher, of mellifera Apis bee of the cities of Codó and Itapecuru-Mirim, pertaining to the region of the Cocais, Maranhao State. It observed in the first, collected in such a way for the producer how much for the researcher, presented a bigger water text (average humidity of 21,05%) when compared with the second (20.98%), making it difficult its storage, therefore the high water text of the product diminishes its useful life of shelf. For total acidity, the value highest was for the honey produced in Codó (79.19% to 91.80% b), when compared with the honey produced in Itapecuru-Mirim (37.78% to 48.36% b), what it can be explained by the temperature difference, being higher in Codó, For the values of pH the honey of Itapecuru_Mirim was gotten presenting lower value (3,2). For reducing sugars, the honey of Itapecuru - Mirim it presented average of next values (64.14% b - 64.20%) to the demanded minimum as standard. For the values of sacarose the samples of Codó, had presented minors average values of (23.59% b 24.29%); in the parameter you sweeten totals the samples of Itapecuru_Mirim presented greater average index (93,73). For the HMF analyses the samples of Codó had presented average values (67,77a the 76,33b). For the too much studied parameters it did not have significant difference between treatments.